Tuning the nucleation kinetics of phosphate chemical conversion coating on Mg-Gd-Y-Zr magnesium alloy: The effect of pretreatment and organic additive - Siyu Sun; Peng Zhou; Yan Chen; JinTao Xiao; Jingli Sun; Yong Yuan; Tao Zhang; Fuhui Wang (Journal of Magnesium and Alloys)
In order to obtain a more protective phosphate conversion coating with a denser architecture, the nucleation kinetics of phosphate chemical conversion coating on Mg-Gd-Y-Zr magnesium alloy was tuned in this work. A pretreatment process was proposed and organic additives were incorporated, which aims at increasing the ionic produce (Jsp) at the interface for increasing σ, and decreasing the critical ionic product (JC,sp), respectively. Results prove that the pretreatment of bare alloys in a phosphate bath could increase the ion products of MgHPO4 / MnHPO4. The addition of benzalkonium chloride could neutralize the charges of crystals, and in turn promote the nucleation kinetics. A denser and more protective conversion coating could consequently be obtained.